Análisis e implementación de algoritmos para distorsionar imágenes con distintos tipos de ruido y aplicación de filtros en dos dimensiones para restaurarlas - García Chilán, Carlos César (2010)
This work analyses some algorithms for image degradation (noise aggregation) and image enhancement using predefined 2D filters. The filtering is a very useful tool in real situation. We will do an qualitative analysis using the Mean Square Error (MSE) that will allow us to determine which filter is more efficient under certain conditions; then we will do an quantitative analysis using human perception of randomly selected people that will determine which filter give the best result in image enhancement and distortion recovery. Finally we will compare the quantitative and the qualitative results.